Islamic Law and the Problems of Society in Terms of Leadership (Politics) - Lestari, Rahman Ilham; Andaryuni, Lilik (International Journal on Advanced Science, Education, and Religion, 2025)
This research examines the concept of Islamic law's crucial role in shaping the direction of national legal policy in Indonesia. This is due to the fact that the majority of Indonesia's population is Muslim, and therefore, Islamic values naturally influence various aspects of national and state life, including the process of formulating legislation. Islamic values, derived from sharia and fiqh, prioritize the principles of justice, welfare, and morality, which align with the state's objectives as outlined in the Preamble to the 1945 Constitution. From an Islamic perspective, leadership is a sacred mandate, not merely a political office. Leaders must be able to realize social justice and the welfare of the people, and be exemplary in upholding religious values. However, the political reality in Indonesia shows that this idealism is often hampered by transactional political practices, such as money politics. Money politics creates a market for support that undermines the democratic process, as people's votes are treated as a commodity to be bought. As a result, many leaders are elected not because of their capabilities and integrity, but because of their financial resources. This reinforces corrupt power structures and is far from the spirit of justice as taught in Islam. For this reason, there needs to be consistent efforts to